ANALISIS PENGARUH PERSPEKTIF MANFAAT DAN KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH DALAM MENINGKATKAN MINAT MEREKOMENDASIKAN (Studi pada Bank Jateng Cabang Pembantu Kagok Semarang) - Saputra, Whisnu Adhi (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2014)
The purpose of this research is to test the influences of benefit advantage and service advantageon customer satisfaction to increase word of mouth intention. Using these variables, the usageof these variables are able to solve the arising problem within PT. Bank Jateng Capem KagokSemarang.The samples size of this research is 100 customers PT. Bank Jateng Capem Kagok Semarang.Using the Structural Equation Modeling (SEM). The results show that the benefit advantageand service advantage on customer satisfaction to increase word of mouth intention.The effect of benefit advantage on customer satisfaction are 0,44; The effect service advantageon customer satisfaction are 0,27; and The effect customer satisfaction on word of mouthintention are 0,43.